Micro-flow nanoemulsions for astronaut designer beverages: tested under simulated microgravity and conceptualised for personal nutrition - Schmidt, Svenja (2025)
In this work, a novel space beverage system is proposed, aiming to leverage food variety in space while mitigating space-related health risks. Taking inspiration from current developments in the beverage industry, strategic beverage fortification can provide astronauts with efficacious mounts of bioactive compounds to address space health hazards, while beverage personalization (flavour and nutrients) can help alleviate menu fatigue and address individual nutrient requirements.